Assessment of Obesity and Cardiometabolic Status by Integrase Inhibitor Use in REPRIEVE: A Propensity-Weighted Analysis of a Multinational Primary Cardiovascular Prevention Cohort of People With Human Immunodeficiency Virus. (20th November 2021) - Kileel, Emma M; Lo, Janet; Malvestutto, Carlos; Fitch, Kathleen V; Zanni, Markella V; Fichtenbaum, Carl J; Overton, Edgar T; Okeke, Nwora Lance; Kumar, Princy; Joao, Esau; Aberg, Judith A; Martinez, Esteban; et al.
Abstract: Background: Emerging data demonstrate that the use of integrase inhibitor (INSTI)-based antiretroviral treatment (ART) is associated with increased weight, but the cardiometabolic health consequences of increased weight remains poorly understood. Methods: This analysis examined INSTI use (>6 months) at entry among REPRIEVE participants enrolled in High Income and Latin America/Caribbean Global Burden of Disease regions. Primary analyses used linear and logistic regression; secondary analyses used quantile regression to examine differences across the full data distribution. Characteristics of those with and without INSTI use were balanced using inverse probability of treatment weighting. Results: Among 4500 REPRIEVE participants, 1848 were on an INSTI-based regimen at entry for an average of 2.1 ± 1.8 years. Integrase inhibitor use (vs no INSTI use) was associated with higher odds of obesity (odds ratio [OR], 1.63; 95% confidence interval [CI], 1.4–1.9) and higher mean body mass index ([BMI] +1.5kg/m2; 95% CI, 1.0–1.9) and waist circumference (+3.6cm; 95% CI, 2.6–4.6). Differences in weight related to INSTI use were greater in the upper tails of the distribution (+3.1kg/m2 [95% CI, 1.9–4.4] at the 90th centile vs +0.7kg/m2 [95% CI, 0.2–1.2] at the 50th centile) and among women and nonwhite participants, with sex and race having an additive effect on BMI. Conversely, INSTI use was not associated with differences in glucose, low-density lipoprotein cholesterol, or higher odds of metabolic syndrome or hypertension. Conclusions: Differences in weight and waist circumference associated with INSTI use are (1) not uniform across people with human immunodeficiency virus, (2) greatest among women and nonwhites, and (3) concentrated at the upper tails of weight distribution. These data identify at-risk subgroups for whom long-term cardiovascular disease outcomes should be carefully assessed. Abstract : INSTI-based regimens are associated with higher weight but not with increased cardiovascular risk for most INSTI users. Differences in weight are not uniform across PWH, and specific subgroups of INSTI users should be monitored for long-term CVD outcomes.